Compliance with Society Guidelines in COVID-19: A Survey on Members of Society of Dermatologists, Venereologists and Leprologists of Nepal - Paudel, Upama; Parajuli, Sudip (Journal of Institute of Medicine Nepal, 2023)
Introduction: COVID-19 pandemic affected the practice of dermatologists of Nepal. The Society laid down the guidelines for safe practice in the interest of its members and patients based on the available evidence at that time. The aim of this study was to assess the compliance of members to its guidelines. Methods: This was a descriptive cross-sectional study carried out from 1st June 2020 to 1st July 2020 by circulating questionnaire via Google form to dermatologists who were members of Society of Dermatologists, Venereologists, and Leprologists of Nepal. The mstudy variables included personal details of the participants and questionnaires related to guidelines. The responses of participants were collected, and descriptive analysis of the data was done. Results: Out of 200 members at the time of study who were sent the mail, only 90 (45%) members responded to the questionnaire. Out of all these respondents, 76 (84.4%) were following the guidelines laid down by the society. Only 43 (47.8 %) of the respondents had deferred patients of outpatient department as per the guidelines. Out of all respondents, 60 (66.7%) had attended dermatological emergencies and triage was done by 50 (55.6%) members. Conclusion: The study showed that most of the members who were responsive to the survey questions sent to them were compliant with the guidelines laid down by the society.